HOW DEMOCRACY IS ELECTION? REASSESSING ARTICLE 18 (4) OF THE 1945 CONSTITUTION AND ITS IMPLICATION TO THE REGIONAL HEAD ELECTION IN INDONESIA - Muhammad Bahrul Ulum (Jurnal Hukum dan Peradilan, 2019)
This paper aims to reassess the term “elected democratically” in Article 18 (4) of Indonesia’s revised 1945 Constitution which resulted in the competing interpretation over the appropriate method for selecting heads of regional governments in Indonesia. In fact, the flexibility of such a term was challenged and negotiated to formulate an appropriate mechanism to select heads of regional governments. In 2004, the Constitutional Court concluded that the legislative body was the ultimate institution to interpret “elected democratically” so that this institution can opt whether a regional head election or an indirect election to define such a term. While the regional head election was applied, including its dispute settlements over electoral results to the Constitutional Court, this Court considered a different argument. In 2013, the Constitutional Court reinterpreted such an article by highlighting that the regional head election should be exempted from the general election subjected to Article 22E (2) of 1945 Constitution. In 2014, President Yudhoyono’s rejection from his agreement after the enactment of the Selection of Heads of Regional Governments Bill put further juridical contentions in which the President finally revoked the adoption of the regional head voting by the Regional People’s Representative Council or Dewan Perwakilan Rakyat Daerah (DPRD). As a consequence, the regional head election has been re-adopted and this regional election has remained to be expected to improve the performance of local democracy. The introduction of this direct election model at the regional level, however, questions the important role of political parties because the adoption of this election was substantially to answer public distrust against them. In particular, the debate whether political parties work becomes intense after non-party candidates are allowed to contest to this election.